Sintesis Sains Dan Al-Qur’an Sebagai Upaya Berpikir Inovasi Dalam Berwirausaha - Yusuf, Sitti Rabiah (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this study is to develop terms and formulate ways of innovation in entrepreneurship for Islamic economic actors. The problem of this research is how to think about innovation used by entrepreneurs so that it has an impact on the development of the Islamic economy. To answer these problems used a qualitative approach to the method of content analysis. The object of research is the textual Al-Qur'an, synthetic thinking books, creativity and innovation books. Research result; 1) The technique of understanding the Qur'an through the synthesis of hadith, verses, theory and individual experience is then abbreviated as HATI 2) Synthesis between science and the Qur'an is then abbreviated as SSQ (synthesis of science and Qur'an 3) SSQ is development of terms from the halal industry, Islamic finance and Islamic economics which contain a synthesis model of thinking innovation in entrepreneurship. These findings will later be continued in the final dissertation of the Islamic economics doctoral program using imindmap.